(untitled) (Comillas Journal of International Relations, 2021)
This paper has two axes. First, it seeks to recover the most relevant concepts of the relationship between politics and democracy. For this reason, some key concepts of Jacques Rancière and Gianfranco Pasquino are included. In a second part, Ernesto Laclau’s concepts on populism will be brought into play to complete the conceptual framework with which the case of Bolivia, in its constitutive stage, is recognized as a contemporary experience of populism, specifically as a case of ethnic populism.